Mycobacterium bovis Induces Endoplasmic Reticulum Stress Mediated-Apoptosis by Activating IRF3 in a Murine Macrophage Cell Line - Cui, Yongyong; Zhao, Deming; Sreevatsan, Srinand; Liu, Chunfa; Yang, Wei; Song, Zhiqi; Yang, Lifeng; Barrow, Paul; Zhou, Xiangmei (Frontiers in Cellular and Infection Microbiology, 2016)
Abstract: Mycobacterium bovis (M. bovis) is highly adapted to macrophages and has developed multiple mechanisms to resist intracellular assaults. However, the host cells in turn deploy a multipronged defense mechanism to control bacterial infection. Endoplasmic reticulum (ER) stress-mediated apoptosis is one such primary defense mechanism. However the role of interferon regulatory factor 3 (IRF3) between ER stress and apoptosis during M. bovis infection is unknown. Here, we demonstrate that M. bovis effectively induced apoptosis in murine macrophages. Caspase-12, caspase-9 and caspase-3 were activated over a 48 h infection period. The splicing of XBP-1 mRNA and the level of phosphorylation of eIF2α, indicators of ER stress, significantly increased at early time points after M. bovis infection. The expansion of the ER compartment, a morphological hallmark of ER stress, was observed at 6 h. Pre-treatment of Raw 264.7 cells with 4-PBA (an ER stress-inhibitor) reduced the activation of the ER stress indicators, caspase activation and its downstream poly (ADP-ribose) polymerase (PARP) cleavage, phosphorylation of TBK1 and IRF3 and cytoplasmic co-localization of STING and TBK1. M. bovis infection led to the interaction of activated IRF3 and cytoplasmic Bax leading to mitochondrial damage. Role of IRF3 in apoptosis was further confirmed by blocking this molecule with BX-795 that showed significant reduction expression of caspase-8 and caspase-3. Intracellular survival of M. bovis increased in response to 4-PBA and BX-795. These findings indicate that STING-TBK1-IRF3 pathway mediates a crosstalk between ER stress and apoptosis during M. bovis infection, which can effectively control intracellular bacteria.